Frangochiotika books from the Eugène Dalleggio collection at the Gennadius Library - Solomonidi, Irini (The Historical Review/La Revue Historique, 2025)
This bibliographic study, presented at the December 2023 workshop “On Languages and Scripts in the Ottoman Levant: The Case of Frangochiotika”, provided an opportunity to explore the Gennadius Library’s lesser-known collections. Through meticulous examination, I identified and presented Frangochiot editions, laying the foundation for an initial corpus of these works. The Gennadius Library, reflecting its founder Joannes Gennadius’ interest in Hellenism and the multiculturalism of Asia Minor, holds 91 Frangochiot editions (1602–1958). Of these, 18 were part of Gennadius’ original 1922 donation, while 73 were gifted by bibliographer Eugène Dalleggio. Dalleggio’s thorough documentation of 128 Frangochiot editions, with 73 copies integrated into the library, enabled the tracing of the collection’s evolution, and highlighted the library’s role in preserving Greece’s heritage. This study aims to lay the groundwork for an online database of Frangochiot books, promoting further research into their historical and cultural significance.